An Analysis of Technological Content Knowledge (TCK) of English Teachers in Vocational High School - Fauziah, Salsabila; Nasrullah, Nasrullah; Asrimawati, Inayati Fitriah (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2023)
Technological Content Knowledge (TCK) is the knowledge of integrating technology into learning materials. The previous research examined TCK in many fields of education, such as history, elementary school teacher education, mathematics, biology, and science. However, TCK study in the English field is still under-researched. Therefore, this study aims to find the English teacher's knowledge of TCK. This study employed a qualitative approach with narrative inquiry design. The researchers used interviews, observation, and documentation to collect the data. The samples of this study are three English teachers in vocational high schools recruited based on several criteria determined by researchers. The finding showed that all participants mastered various technologies to deliver learning and could combine the two things well to achieve learning objectives. It can be concluded that all participants have a good level of knowledge of TCK.